Randomization of Left-right Asymmetry and Congenital Heart Defects: The Role of DNAH5 in Humans and Mice - Nöthe-Menchen, Tabea (Circ Genom Precis Med, 2019)
BACKGROUND: Nearly one in 100 live births presents with congenital heart defects (CHD). CHD are frequently associated with laterality defects, such as situs inversus totalis (SIT), a mirrored positioning of internal organs. Body laterality is established by a complex process: monocilia at the embryonic left-right organizer (LRO) facilitate both the generation and sensing of a leftward fluid flow. This induces the conserved left-sided Nodal signaling cascade to initiate asymmetric organogenesis. Primary ciliary dyskinesia (PCD) originates from dysfunction of motile cilia, causing symptoms such as chronic sinusitis, bronchiectasis and frequently SIT. The most frequently mutated gene in PCD, DNAH5 is associated with randomization of body asymmetry resulting in SIT in half of the patients; however, its relation to CHD occurrence in humans has not been investigated in detail so far. METHODS: We performed genotype / phenotype correlations in 132 PCD patients carrying disease-causing DNAH5 mutations, focusing on situs defects and CHD. Using high speed video microscopy-, immunofluorescence-, and in situ hybridization analyses, we investigated the initial steps of left-right axis establishment in embryos of a Dnah5 mutant mouse model. RESULTS: 65.9% (87 / 132) of the PCD patients carrying disease-causing DNAH5 mutations had laterality defects: 88.5% (77 / 87) presented with SIT, 11.5% (10 / 87) presented with situs ambiguus; and 6.1% (8 / 132) presented with CHD. In Dnah5(mut/mut) mice, embryonic LRO monocilia lack outer dynein arms resulting in immotile cilia, impaired flow at the LRO, and randomization of Nodal signaling with normal, reversed or bilateral expression of key molecules. CONCLUSIONS: For the first time, we directly demonstrate the disease-mechanism of laterality defects linked to DNAH5 deficiency at the molecular level during embryogenesis. We highlight that mutations in DNAH5 are not only associated with classical randomization of left-right body asymmetry but also with severe laterality defects including CHD.